Komunikasi Interpersonal Penyidik Untuk Mengungkapkan Pengakuan Tersangka Tindak Pidana Narkotika Di Direktorat Reserse Narkoba Polda Nusa Tenggara Barat - Ni Kadek Ana Sugitawati; Ni Putu Listiawati; I Kayan Kariyadi (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2019)
In upholding a problem to uphold justice, narcotics circulation in the current era is increasing very rapidly compared to before. One contributing factor is the development of technology and affordability of the prices of these prohibited narcotics goods. The purpose of this study is to find out and analyze the obstacles faced by investigators in conducting interpersonal communication against Narcotics criminal suspects. This type of research used in this thesis is qualitative. Qualitative research in the form of research with the method or case study approach (case study). In this study, researchers used data collection techniques with in-depth interviews, observation, and documentation. The findings in this study are that an investigator has applied interpersonal communication to the suspect at the beginning or before the examination. Making it easier to reveal the suspect's network or disclose the suspect's status in the narcotics case he did. Can be described as a suspect classified as pure pemekai, victims, or just a narcotics offender for themselves or dealers and others.